Risk Factors for Stunting in Children Aged 24 – 60 Months in Cilegon City - Juliawita Andrieni; Syahrizal Syahrizal (Ridwan Institute, 2023)
Stunting is a disturbance of growth and development in children due to chronic malnutrition and recurrent infections. Child stunting can occur within the first 1000 days after conception and is related to many factors, namely context factors and causative factors. This study wanted to find out the causal factors for stunting in Cilegon City by using e-PPGBM data for August 2022 in the age group 0-60 months. The study was conducted using a case-control design. The inclusion criteria were children aged 24 -60 months with complete data. The research sample consisted of 819 subjects, with 273 stunted subjects and 546 non-stunted subjects. In multivariate analysis it was found that LBW (Low Birth Weight) has a risk of stunting 3.24 times compared to normal birth weight and undernourished status has a risk of 2.04 times stunting than good nutrition at 95% CI aOR with p value <0.001. The risk factors for gender, LBL (Low Birth Length), vitamin A status and exclusive breastfeeding were not related to stunting in this study.